2017
DOI: 10.15517/psm.v15i2.31634
|View full text |Cite
|
Sign up to set email alerts
|

Imagen corporal y representaciones alimentarias en mujeres de trece comunidades rurales mexicanas

Abstract: problema de salud pública, particularmente en la población femenina; el aumento de otros padecimientos como anorexia y bulimia; y el incremento de la preocupación por el cuerpo, que lleva a transformar algunas prácticas y representaciones alimentarias no solo en población urbana, sino en mujeres de las zonas rurales. Objetivos: tener un primer acercamiento a la percepción corporal de las mujeres de las zonas rurales, conocer cómo son, cómo se perciben y cómo les gustaría ser, e identificar algunas de sus repre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
2
1
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 5 publications
(10 reference statements)
0
2
0
1
Order By: Relevance
“…In this regard, the researchers report that "dislike of the body", expressed by the interviewees and related more to an aesthetic motive than to health, is increasing in rural communities, and therefore invites reflection on how medical, family, community and media discourses have influenced their social representations of the body. 25 When results are compared, in relation to the level of body image dissatisfaction, with those obtained in populations from urban areas, it be seen that there is no significant variation and that the tendency to thinness is shared by both contexts, for example, in a study carried out in three Chinese communities, one of them rural, it was found that the participants from the three communities had a desire for a slimmer figure in addition to sharing the concern about the consumption of fats, which is why the researchers mention that those are phenomena more related to modernity than to ethnicity. 35 An important aspect to consider is the inclusion of both genders in the study samples, allowing the possibility of finding that body dissatisfaction is a phenomenon shared by men, who may even be presenting a higher level of dissatisfaction than women, 24,37 a similar situation presented in urbanized areas.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this regard, the researchers report that "dislike of the body", expressed by the interviewees and related more to an aesthetic motive than to health, is increasing in rural communities, and therefore invites reflection on how medical, family, community and media discourses have influenced their social representations of the body. 25 When results are compared, in relation to the level of body image dissatisfaction, with those obtained in populations from urban areas, it be seen that there is no significant variation and that the tendency to thinness is shared by both contexts, for example, in a study carried out in three Chinese communities, one of them rural, it was found that the participants from the three communities had a desire for a slimmer figure in addition to sharing the concern about the consumption of fats, which is why the researchers mention that those are phenomena more related to modernity than to ethnicity. 35 An important aspect to consider is the inclusion of both genders in the study samples, allowing the possibility of finding that body dissatisfaction is a phenomenon shared by men, who may even be presenting a higher level of dissatisfaction than women, 24,37 a similar situation presented in urbanized areas.…”
Section: Discussionmentioning
confidence: 99%
“…The selected studies have diverse origins, with the majority of the work being carried out in the United States of America [11][12][13][14][15][16] , Mexico, [17][18][19][20][21][22][23][24][25][26] and Africa. [27][28][29][30][31] To a lesser extent, works from Australia, 32 Canada, 33 Spain, 34 China, 35 Chile, 36 and India.…”
Section: Characteristics Of the Studiesmentioning
confidence: 99%
“…Pacheco, Mota y Luna (2017) nicipios de alta y muy alta marginación en el estado de Oaxaca realizado con niños menores de 5 años, encontró que 1.8% de los niños tenían problemas de desnutrición, y 5.4% presentaba problemas de obesidad. En otro estudio con mujeres rurales de 7 estados de la república, se encontró un fuerte problema de malnutrición al obtener que 9.6% de las mujeres estaban delgadas, pero 29.4% presentaba sobrepeso y 28% obesidad (Pérez y Romero, 2018). La desnutrición y la obesidad se encuentran presentes en la población en condiciones de pobreza.…”
Section: Introductionunclassified